Strengthening Youth Resilience to Radicalization : Evidence from Tajikistan - World Bank (World Bank, Washington, DC, 2020)
The report provides the first primary research conducted in Tajikistan by the World Bank Group (WBG) to analyze the youth, gender and local dimensions of radicalization and recruitment by VE groups, helping fill a gap in such analysis and evidence. It is based on qualitative research conducted across Tajikistan in 2018 and builds on the government of Tajikistan's official statistics as well as existing literature on socio-economic conditions and violent extremism in the country. The research provided critical inputs to three projects under the Resilience Strengthening Program (RSP3) which is supported by the IDA-18 Risk Mitigation Regime through a contribution close to US100 million dollars. In particular, this study informed the design of the 37 million dollars Socio-Economic Resilience Strengthening Project, an intervention that focuses on vulnerable communities and youth groups along border areas with Afghanistan. This report also seeks to contribute to the global understanding of radicalization and violent extremism, particularly in the context of the first pillar of the WBG Strategy for Fragility, Conflict and Violence 2020-2025 focusing on preventing violent conflict and interpersonal violence.